2019
DOI: 10.34239/ajops.v2i1.72
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable temporising matrix for necrotising soft tissue infections: a case report

Abstract: Necrotising soft tissue infection (NSTI) is a rapidly progressing disease that presents a surgical emergency. Timely antibiotics, radical debridement of infected tissues and adjuvant hyperbaric oxygen therapy are the foundations of its treatment. Split-skin graft (SSG) is the main reconstruction technique due to its simplicity and dependability. Dermal substitutes, as well as creating a suitable wound bed for grafting, aim to recreate the inherent thickness and pliability of skin. One innovation, Novosorb™ (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…However, establishing a neo-dermis enhances structural stability and provides the time required for definitive epithelial wound closure, whether by serial grafting or by generating and applying autologous engineered skin. The NovoSorb TM Biodegradable Temporising Matrix (BTM) is a synthetic scaffold that is currently in routine use for burns and complex wound repair (73)(74)(75)(76)(77)(78)(79). It is a scaffold that temporises the wound and biodegrades after integration and establishment of dermal elements (80).…”
Section: Large Excised Wounds-temporising the Wound Bed For Definitive Closurementioning
confidence: 99%
See 2 more Smart Citations
“…However, establishing a neo-dermis enhances structural stability and provides the time required for definitive epithelial wound closure, whether by serial grafting or by generating and applying autologous engineered skin. The NovoSorb TM Biodegradable Temporising Matrix (BTM) is a synthetic scaffold that is currently in routine use for burns and complex wound repair (73)(74)(75)(76)(77)(78)(79). It is a scaffold that temporises the wound and biodegrades after integration and establishment of dermal elements (80).…”
Section: Large Excised Wounds-temporising the Wound Bed For Definitive Closurementioning
confidence: 99%
“…It is a scaffold that temporises the wound and biodegrades after integration and establishment of dermal elements (80). Furthermore, it resists infection, can be made in large sheets, is inexpensive to produce, easy to handle, and provides integration time (76)(77)(78)(79)(80)(81)(82). With the optimisation of a dermal replacement template and a major limitation addressed, i.e., acquisition of time for cellular growth, the prospective next step is the specification of a definitive wound closure alternative.…”
Section: Large Excised Wounds-temporising the Wound Bed For Definitive Closurementioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 12 This success led to its use in necrotising soft tissue infections to provide pliable wound coverage. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…The use of BTM in burns demonstrated that it could successfully treat large total body surface area burns with excellent cosmetic and functional results 3,12 . This success led to its use in necrotising soft tissue infections to provide pliable wound coverage 13,14 …”
Section: Introductionmentioning
confidence: 99%